Management Challenges: Resection or Observation due to Astigmatism Refractive Error Associated with a Pediatric Limbal Dermoid Lesion - Rahmaniyah, Aisyah; Fatmariyanti, Susy; Deneska, Ria Sandy (Universitas Airlangga, 2025)
Introduction: Limbal dermoid is a congenital benign tumor that contains choristomatous tissue, which may cause astigmatism and lead to amblyopia. This presents management challenges related to limbal dermoids, astigmatism, and amblyopia. Case Presentation: A 10-year-old girl complains of a tumor in the left eye that appeared since two months old, initially small and gradually enlarged. The patient has blurred vision, especially during study. Visual acuity of the right and left eye is 0.33 and 0.15 with best correction visual acuity with left lens power C-3.00 x 10 to 0.67 and right lens power C-7.00 x 0 to 0.33. Anterior segment examination of the left eye revealed a hairy, light brown, soft, solid mass that measured 8 mm x 5 mm x 3 mm located at the limbus and widened towards the cornea and bulbous conjunctiva. Conclusions: Surgery does improve the physical appearance, but unless the young person receives treatment soon, the astigmatic error and visual acuity may not change considerably.